Factors influencing purchase intention and loyalty towards private label products - Raposo, Rita Bárbara de Sousa Faria Simões (2023)
Private labels entered the market approximately seven decades, and began to be perceived as cost-effective, trivial, and of lower quality when compared to their national brand counterparts. Nowadays, these labels have established a dominant presence within the global Fast-Moving Consumer Goods (FMCG) sector and become strong competitors to national brands. This paradigmatic shift has profoundly reshaped consumers ‘perceptions and subsequent interactions with these brands. However, it is still unclear in the literature which qualities private labels shall have to be consumers' first choice rather than their secondary option, which is typically the case. This dissertation aims to address this research gap by investigating the factors that influence consumers' purchasing intentions and loyalty towards private labels. Following an extensive review of the relevant literature, a qualitative methodology was applied to collect and analyze the data. Two focus group discussions were conducted among millennial consumers in Portugal. The research findings have identified four key factors directly impacting consumers´ purchase intentions for private labels: reference price discrepancy, perceived value for money, perceived product quality, and store image. Furthermore, this study postulates that in-store private label positioning and packaging design and labelling positively contribute to perceived product quality. It was also revealed that perceived value for money, perceived product quality, and store image have a substantial impact on consumer loyalty towards private labels. Reference price discrepancies were not found as significantly affecting consumer´s loyalty towards private labels. It is worth mentioning that in-store national brand promotions were recognized as a predominant barrier that dissuades consumers from choosing private-label products. These findings offer significant implications in the fields of marketing and retail, providing valuable insights for practitioners and scholars.